POTENCY OF KIPO, A TRADITIONAL FOOD FROM KOTAGEDE – YOGYAKARTA - Wahyu Supartono; Siti Mauna; Adi Djoko Guritno (Agroindustrial Technology, University of Trunojoyo Madura, 2010)
Kipo is a traditional food from Kotagede Region – Yogyakarta, which is produced from glutinous rice. It was processed through some steps such as weighing, mixing, melting, roasting and packing. This traditional food is not popular like other traditional foods such as gudeg or yangko. Problems concerning this situation were, the information of kipo was not well delivered to the consumers and people who were doing business with kipo were very limited and only in Kotagede.This research was aimed to disclosure the potency of kipo, if it was developed as industrial foods. The aspects of market, technical and financial were conducted and analyzed. These aspects were used for giving considerations, if this product could be developed in the future. The results depicted, that from the market aspect, value kipoconsumer’s attitude index was good (3.8845 from 5). The technical aspect showed, that this industry was quite small scale with processing capacity only 19 kg product per day, used 5 menpower and 60 m2 area.Based on the financial aspect at actual capacity, the results showed Net Present Value was Rp. 70,180,679; Payback Period 1.21 years; Profitability Index 5.51;Internal Rate of Return 98.5% and Break Even Point was Rp. 505,414 or 212,693 kipo. This industry was very sensitive to the increase of interest level, total cost and decrease of price product. Some challenged aspects of kipo were, it was produced from naural sources such as glutinous rice, coconut, brown sugar and also natural food colouring agent. The traditional process was still kept and the people could enjoy how it was produced. This is the challenge to develop the traditional food as part of culinary or historical tour.